Papa, please get the moon for me - Carle, Eric (New York : Simon & Schuster Books for Young Readers, 1986)
Monica's father fulfills her request for the moon by taking it down after it is small enough to carry, but it continues to change in size. Some pages fold out to display particularly large pictures.
Keywords: Toy and movable books-Sepcimens; Moon-Fiction; Toys and movable books